Electrostatic field theoretic approach to analyze the partial discharge phenomenon pertaining to insulation degradation - Mukherjee, Shubhankan; Chattopadhyay, Adhir Baran; Thomas, Sunil (International Journal of Engineering and Technology, 2018)
This paper elucidates the application of electrostatic field theory to analyze partial discharge due to the void formation inside the insulating material. Formation of voids leads to accumulation of static charges leading to capacitance build-up. The most probable cause of insulation failure is due to the subjection of high voltage. Prolonged high voltage poses a threat and leads to insulation failure. Failures occur in the tip gap between the conductor and insulating material’s inner periphery. Probable causes of such failures are corona discharge, surface discharge and treeing, leading to formation of Lichtenberger figures in the material and cavity discharge. This paper presents a way of fabricating the inner lining of the insulator with a semiconductor layer obeying avalanche breakdown at breakdown voltage or voltages at which partial discharge is likely to occur. With the onset of high voltage which can cause a discharge, the semiconductor experiences avalanche breakdown giving out a single photon ejection by Geiger mode (principle). A superior prevention method of using Teflon for insulation instead of XLPE/PILC has been suggested and simulated using COMSOL. Detection using Avalanche photo-detector(LiDAR) may enable us to track the probable location of the occurrence of partial discharge and isolate the system.